Development and evaluation of a self-directed pediatric clinical elective course using the learning contract - Arcadio, Ramon L. (1990)
The study described a pioneering effort in the development and evaluation of a self-directed pediatric clinical elective course in the INTARMED Curriculum of the College of Medicine, University of the Philippines. A thorough investigation of the considerations, steps, difficulties and evaluation of the self-directed learning approach was done. The study reflected the efforts of introducing a curricular innovation where there is an emphasis on the student and learning as opposed to the traditionalist emphasis on the teacher and teaching. At the end of the study, an instructional design was developed which described the appropriate steps in implementing a self-directed course, and these are: 1) orientation and climate-setting; 2) self-assessment of learning needs and interests; 3) formulating the behavioral objectives; 4) designing the preliminary learning contract; 5) self-management of learning; 6) evaluating the learning outcomes. The course received a favorable assessment from both faculty and students. Based on this developmental experience, the self-directed learning approach is recommended for use in various medical disciplines to translate the curriculum from the old teacher-directed approach into successful student-centered instructional programs. It is likewise recommended for use in the residency and post-residency fellowship programs where an individualized learning approach is appropriate.
Special project (Master of Health Professions Education)--University of the Philippines Manila
Keywords: Pediatrics -- Study and teaching (Residency)